EFEK DOMINO DARI PERANG DAGANG AS-CHINA TERHADAP PEREKONOMIAN INDONESIA - deaa, Dear Filzah Nurhaeni (Journal Social Politica, 2025)
This research aims to analyze the domino effect caused by the US-China Trade War on the Indonesian economy. This research uses the concept of domino effect and the approach of international political economy theory and hegemony theory, as well as literature study method with descriptive-qualitative analysis. The findings show that the trade war that occurred between the United States and China in 2018-2024 had a significant influence on the international scope of the economy, including influencing the economy in Indonesia as well. The domino effect that occurs in Indonesia, consists of changes in exchange rates, decreased exports, diversion of investment, and creating new opportunities for Indonesia. In addition, global economic uncertainty has caused the value of the rupiah currency to be depressed since 2018. Although Bank Indonesia intervened and implemented monetary measures to maintain stability. However, the movement of the rupiah exchange rate in 2021-202 is still in the weak category due to the development of trade wars, changes in the direction of interest rate policy at the global level, and uncertainty in world economic conditions.